Inteligencias múltiples en estudiantes de tercer grado de secundaria de una institución educativa de Ventanilla - Callao - Matos Caparó, Félix Martín (2012)
The descriptive research consisted of measuring the multiple intelligences, defined by Gardner (2001), of one hundred and thirty-three students from third grade secondary a school of Ventanilla - Callao in 2010. The instrument applied is The Minds Multiple Intelligences Scale validated in Peru by Ruiz (2004). The result indicates high levels in the kinesthetic, interpersonal and naturalist intelligences as well as low levels of the mathematical and linguistic intelligences. The application of the instrument contributes to the description of the multiple intelligences and the grouping students according to intelligences patterns for high, medium and low levels.